Aberrant signaling in tonsillar B cells producing pathogenic O-glycoforms of IgA1 in IgA nephropathy - Yamada, Koshi; Ogiwara, Kei; Novak, Jan; Suzuki, Yusuke (Frontiers in Immunology, 2026)
IgA nephropathy (IgAN) is a mesangioproliferative glomerulonephritis characterized by IgA1-containing immune-complex deposits wherein IgA1 is enriched for galactose-deficient IgA1 (Gd-IgA1) glycoforms. IgAN pathogenesis involves mucosal immune system, as IgAN onset and activity are associated with infections of the upper-respiratory tract, i.e., synpharyngitic hematuria. Current four-hit hypothesis postulates that multiple events, starting with the production of Gd-IgA1, in genetically susceptible individuals lead to the formation of nephritogenic immune complexes and development of IgAN. Biochemical studies using IgA1-producing cell lines derived from the peripheral blood of IgAN patients and healthy controls revealed that secretion of Gd-IgA1 is due to dysregulated expression of several O-glycosylation enzymes. Production of Gd-IgA1 can be further upregulated by some cytokines. Genome-wide association studies identified multiple candidate genes for IgAN, serum levels of IgA, and serum levels of Gd-IgA1. Some of the IgAN-associated genes are also found in other autoimmune diseases and conditions. Notably, HORMAD2/LIF locus is associated with IgAN, serum levels of IgA, and tonsillectomy. In this review, we detail various findings concerning IgAN and Gd-IgA1 production by cells derived from the circulation and tonsils. Also, as tonsillectomy is commonly used in Japan as a part of treatment for IgAN, we detail biochemical and signaling studies of IgA1-producing cells derived from peripheral blood and tonsils.